2018
DOI: 10.3390/su10103744
|View full text |Cite
|
Sign up to set email alerts
|

On Technology in Innovation Systems and Innovation-Ecosystem Perspectives: A Cross-Linking Analysis

Abstract: The purpose of this paper is to clarify the role of technology as it has been framed within Innovation System (IS) and Innovation Ecosystem (IE) literature research streams. The methodological choice is a systemic review that allows to focus on theoretical proposals by scholars and the identification of the commonalities regarding the pivotal role of technology and the differences in describing innovation-based mechanisms in both literatures. Results show that the key elements are the overall idea of technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 120 publications
(151 reference statements)
0
25
0
2
Order By: Relevance
“…Nylund et al (2021) addressed specially the IE for meeting the SDGs considering multinational enterprises. In addition, the main authors addressing both sustainability and IE are Trischler et al (2020), Russell andSmorodinskaya (2018), Yin et al (2020), Yang, Chen, Du, Lin, andLu (2021), Oksanen and Hautamäki (2015), Zeng, Hu, and Ouyang (2017) Amitrano, Tregua, Russo Spena, and Bifulco (2018), J. Huang et al (2020), Gerli, Chiodo, andBengo (2021), Costa and Matias (2020), Tolstykh et al, (2020a, 2020b), and Boyer (2020.…”
Section: Methodsmentioning
confidence: 99%
“…Nylund et al (2021) addressed specially the IE for meeting the SDGs considering multinational enterprises. In addition, the main authors addressing both sustainability and IE are Trischler et al (2020), Russell andSmorodinskaya (2018), Yin et al (2020), Yang, Chen, Du, Lin, andLu (2021), Oksanen and Hautamäki (2015), Zeng, Hu, and Ouyang (2017) Amitrano, Tregua, Russo Spena, and Bifulco (2018), J. Huang et al (2020), Gerli, Chiodo, andBengo (2021), Costa and Matias (2020), Tolstykh et al, (2020a, 2020b), and Boyer (2020.…”
Section: Methodsmentioning
confidence: 99%
“…Dmitriev et al thought that high-tech industry clustering could accelerate the technological innovation of the high-tech industry and lower product cost [11]. By constructing a combing model, Amitrano et al found that the higher the market competition level, the higher the enterprises' technological innovation level [12]. Li et al thought that excess governmental invention would obstruct the improvement of total factor productivity of the high-tech industry [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The systems examined in this research, with the application of the SIS and SF approaches, can be further analysed by using the multi-level perspective [169,170], innovation ecosystems [171], mapping frameworks [172] and risk scoping through the interaction of stakeholders [173,174]. This potential enhancement of the SIS approach would contribute to a broader examination of the systems studied, since the challenges regarding the diffusion of innovation would not be the sole focal point of the research; other aspects could also be investigated, such as landscape factors leading to significant changes in the transportation sector.…”
Section: Discussionmentioning
confidence: 99%